2016
DOI: 10.1007/s10792-016-0284-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the measurements of a novel optical biometry: Nidek AL-Scan with Sirius and a ultrasound biometry

Abstract: To investigate the accuracy of the measurements of Nidek AL-Scan by comparing with Sirius (CSO, Florence, Italy), a corneal tomography which also employs the Scheimpflug principle, and a commonly used device, ultrasound biometry (UB) (Aviso A/B, Quantel Medical, MT, USA). Right eyes of 85 healthy volunteers (58 women 27 men) with a mean age of 39.24 ± 14.37 years (range 15-68) were enrolled into this comparative prospective study. Average K 2.4, average K 3.3, CCT (central corneal thickness), WTW (white to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
3
7
1
1
Order By: Relevance
“…Central corneal thickness measurements with AS‐OCT and Sirius were found to be thicker than optical biometry AL‐Scan measurements in our study. Also, Çağlar et al reported that optical biometry AL‐Scan gives central corneal thickness lower than the Sirius device . Differences between devices have been attributed to different technological methods.…”
Section: Discussionsupporting
confidence: 63%
“…Central corneal thickness measurements with AS‐OCT and Sirius were found to be thicker than optical biometry AL‐Scan measurements in our study. Also, Çağlar et al reported that optical biometry AL‐Scan gives central corneal thickness lower than the Sirius device . Differences between devices have been attributed to different technological methods.…”
Section: Discussionsupporting
confidence: 63%
“…found good agreement with Nidek AL-Scan ® and Sirius in a healthy population. [ 10 ] In our study, there was no good agreement in WTW between Sirius and AL-Scan ® (mean difference = −0.23, P = 0.014).…”
Section: Discussioncontrasting
confidence: 62%
“…enrolled 43 healthy volunteers to evaluate the accuracy of Nidek AL-Scan ® and Sirius and showed that AL-Scan ® tends to measure CCT less than Sirius with the moderate agreement. [ 10 ] However, they did not explain this. We attributed this divergence to alignment differences, measurement area, and study population.…”
Section: Discussionmentioning
confidence: 98%
“…La distancia blanco-blanco, solo es necesaria en algunas fórmulas y es particularmente útil en el cálculo de lentes fáquicos 18,19 .…”
Section: Discussionunclassified